2022
DOI: 10.3390/medicina58020216
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Early Impacts of Post-COVID-19 Pneumonia on Clinical Manifestations, Pulmonary Function, and Chest Radiographs

Abstract: Background and Objectives: Scant data regarding early post-COVID-19 effects are available, especially in younger people. Therefore, the objective of this study was to explore the early clinical impacts of post-COVID-19 pneumonia, comparing severe and non-severe patients. Materials and Methods: A cross-sectional study was conducted in adult patients admitted with COVID-19 pneumonia from April to May 2021. Demographic data, symptoms and signs, quality of life, Hospital Anxiety and Depression Scale (HADS), chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Subjects with CRP levels at the time of treatment are above 90 mg/L, as much as 35 percent, with a median CRP level of 60.45 ( 2.1-330.7) mg/L. This result is similar to the study by Niyatiwatchanchai et al, (2022), which found a median CRP of 67.8 (28, 8-122.6) mg/L. The study by Sirayder et al, (2022) found that the average CRP value for severe COVID-19 was 42.3 ± 46.5 mg/L.…”
Section: Resultssupporting
confidence: 85%
“…Subjects with CRP levels at the time of treatment are above 90 mg/L, as much as 35 percent, with a median CRP level of 60.45 ( 2.1-330.7) mg/L. This result is similar to the study by Niyatiwatchanchai et al, (2022), which found a median CRP of 67.8 (28, 8-122.6) mg/L. The study by Sirayder et al, (2022) found that the average CRP value for severe COVID-19 was 42.3 ± 46.5 mg/L.…”
Section: Resultssupporting
confidence: 85%
“…This shows that in this study, there was no significant difference between the patient's NLR and the results of obstruction spirometry after the patient recovered. There is a study conducted by Niyatiwatchanchai et al it was found that in the acute phase of COVID-19, patients with severe degrees had more lung inflammation than mild or moderate degrees, and increased inflammatory mediators and cytokines with the finding of increased NLR and spirometry examinations were also carried out in post-COVID-19 patients with spirometry results still within normal limits and no differences in spirometry results for differences in disease severity [25]. The neutrophil-lymphocyte ratio is a relationship between innate immunity (neutrophils) and adaptive immunity (lymphocytes) that can be used as a predictor of inflammation to determine the prognosis of inflammation, including COVID-19, where the higher the NLR, the worse the prognosis of the disease [26].…”
Section: Resultsmentioning
confidence: 99%
“…Although widely advocated [ 3 - 5 ], exertional desaturation tests have not yet been validated in patients with COVID-19. Preliminary studies have shown good correlations of 6MWD and ΔSPO 2 with disease severity, diffusion capacity, and lung volumes [ 2 , 15 , 16 ]. 6MWT has been studied in the pre-hospital setting (to assess the need for hospitalization), hospital setting (to determine the discharge readiness), and post-hospital setting (to determine the impact of post-COVID illness) [ 3 , 4 , 6 , 15 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have shown good correlations of 6MWD and ΔSPO 2 with disease severity, diffusion capacity, and lung volumes [ 2 , 15 , 16 ]. 6MWT has been studied in the pre-hospital setting (to assess the need for hospitalization), hospital setting (to determine the discharge readiness), and post-hospital setting (to determine the impact of post-COVID illness) [ 3 , 4 , 6 , 15 , 17 , 18 ]. In this study, we assessed the test's application in discharge-ready patients after recovery from severe COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%